Dietary iron attenuates Clostridioides difficile infection via modulation of intestinal immune response and gut microbiota - Xiao Li; Xiaoxiao Wu; Wanqing Zang; Zhou Zhou; Wenwen Cui; Ying Chen; Huan Yang (Virulence)
Clostridioides difficile (C. difficile) is one of the majors causes of antibiotic-associated diarrhea globally. Host vulnerability to C. difficile infection (CDI) is largely affected by gut microbiota, which in turn is influenced by diet. However, the mechanism underlying the interplay between diet and the gut microbiota that regulates host susceptibility to CDI remains unclear. This study aimed to investigate how a high-iron diet affects the intestinal immune response, microbiota, and metabolism in mice infected with C. difficile. We explored the specific role of the unique gut microbiota and metabolites on CDI. A mouse model of CDI was constructed with or without high dietary iron treatment. The effect of high iron levels on gut microbiota was analyzed by 16S rRNA gene sequencing, and the role of gut microbiota was confirmed by fecal microbiota transplantation (FMT). High dietary iron (400 mg/kg ferrous sulfate) alleviated CDI by decreasing C. difficile pathogenicity and altering host intestinal neutrophil recruitment. Furthermore, E. coli AVS0501, enriched in the gut microbiota of iron-treated CDI mice, showed prophylactic and therapeutic effects on CDI. Moreover, the production of L-proline and tauroursodeoxycholic acid (TUDCA) in CDI mice treated with high dietary iron influenced C. difficile colonization, toxin production, and in turn, regulates the intestinal neutrophil response. Thus, high dietary iron alleviates C. difficile induced enteritis by regulating gut microbiota maintaining gut homeostasis, suggesting that high dietary iron may be an important determinant of disease control.